The Relationship between School Bullying and Self-acceptance in a Sample of Sixth Grade Pupils in Hama City (Journal of Hama University, 2024)
The current study aims at recognizing the level of school bullying and self-acceptance among a Sample of Sixth Grade Pupils in Hama City. It also aims at recognizing the relationship between School Bullying and Self-acceptance for the same sample. In addition, it aims at recognizing the differences between the average means in School Bullying and Self-acceptance according to gender. The sample consists of (389) in Hama City: (186) male/ (203) female. The research has created a scale for School Bullying and another scale for Self-acceptance after conducting the appropriate psychometric studies for both scales.The results of the study are:• There is (average) level of School Bullying among the sample members in the total score of the scale and its sub-dimensions.• There is (average) level of Self-acceptance among the sample members in the total score of the scale and its sub-dimensions.• There is a negative relationship between School Bullying and Self-acceptance among sample members.• There are differences in the means of sample members on the scale of school bullying according to gender for the sake of male members.• There are no differences in the means of sample members on the scale of Self-acceptance according to gender.